Buffer-Stock Saving and Households' Response to Income Shocks - Giulio Fella; Serafin Frache; Winfried Koeniger (Center for Economic Studies and ifo Institute (CESifo), 2016)
We use the Italian Survey of Household Income and Wealth, a rather unique dataset with a long time dimension of panel information on consumption, income and wealth, to structurally estimate a buffer-stock saving model. We exploit the information contained in the joint dynamics of income, consumption and wealth to quantify the degree of insurance against income risk. The estimated model implies that Italian households can insure between 89 and 95 percent of a transitory and between 7 and 9 percent of a permanent income shock. Compared to existing empirical estimates for the same dataset, our findings suggest that Italian households do not have access to significant insurance beyond self-insurance.
Keywords: D91; E21; 330; consumption; wealth; incomplete markets; insurance